THE PLACE OF NEOPETRİN DURING CURRENT AND CELLULAR IMMUN ACTIVATION - BAYRAKTAR, Nihayet; BAYRAKTAR, Mustafa (Göbeklitepe Medical Science Journal, 2021)
Neopterin belongs to the chemical group known as pteridines, it is synthesized by human macrophages upon stimulation with the cytokine interferon-gamma and is indicative of a pro-inflammatory immune state. Measuring blood serum, neopterin concentrations, cellular immune activation in humans especially in various diseases such as infections, autoimmune diseases and malignancies, activation of the immune system is also involved in immunological processes in neurological and cardiovascular diseases. Providing important factors in pathologies and valid treatment is important in monitoring immunological changes in patients. Cellular immune activation can be monitored easily and sensitively by measuring neopterin in biological fluids. In this review, neopterin, one of the current research, has been evaluated. High neopterin production is associated with increased concentrations of reactive oxygen species, neopterin. It also valus to estimate the extent of oxidative stress caused by the immune system. As a result; In this review, the increase in neopterin concentrations in biological fluids such as patient urine and serum is an important marker in the diagnosis and treatment of various diseases.